Drag and Drop : Pelatihan Penerapan IoT Berbasis MIT APP Inventor pada Kelompok Mahasiswa PTA 2022 - Ashadi, Ninik Rahayu; Risal, Ahmad; Suhaeb, Sutarsi; Hamda, Hamda; Kaseng, Ernawati S. (Jurusan Teknik Informatika dan Komputer, 2025)
The purpose of this community service is (1) to provide an understanding of the basic concepts and IoT Architecture by the 2022 PTA student group, (2) to provide an understanding and practice of optimal use on the APP inventor platform so as to slow down the process and implementation of IoT. The implementation of this community service for 2 days with the following methods: (1) lectures, (2) questions and answers, (3) practice. Based on the results of the community service, it can be concluded that several things that are indicators of success during the community service are that (1) During the training, in the process of providing material and simulation, training participants gain experience in understanding concepts and how to simulate the App Inventor through providing material and application simulations, (2). In the training process, the motivation of the training participants is very enthusiastic or is included in the high category, it can be seen that the target for training participants is 100% present, (3). In the training process at the evaluation stage, training participants have been able to design or create supporting applications using the App Inventor.